MERANCANG ULANG PEDOMAN PENULISAN SKRIPSI: MENGATASI TANTANGAN DAN MEMASTIKAN STANDAR KUALITAS UNGGUL BAGI MAHASISWA PENDIDIKAN ISLAM ANAK USIA DINI DI UIN AR-RANIRY - Fajriah, Heliati; Puspa Juwita, Rani; Naufal Fadhil (Bunayya, 2026)
Students of the Islamic Early Childhood Education (PIAUD) Study Program at UIN Ar-Raniry face challenges in preparing their final projects, such as inconsistent formatting and difficulty generating research ideas (58.47%). This study aims to redesign the final project writing guidelines using the 4D development model (Define, Design, Development, Disseminate). Data collection techniques included a needs analysis in the Define stage, the use of expert validation instruments (a 4-point Likert scale) in the Development stage, and the distribution of user trial questionnaires using snowball sampling in the Disseminate stage. The Design stage produced an innovative guideline draft that includes tips for starting the writing process, a complete Standard Operating Procedure (SOP), and guidance on the article-based pathway. Validation by three experts yielded the following results: a linguist expert score of 92.5% (highly feasible), a media expert score of 100% (highly feasible), and a content expert score of 79.69% (feasible). The small-scale trial involving 15 students produced an average score of 3.5, while the large-scale trial involving 50 students obtained scores above 3.7. The final product, in the form of a guideline handbook, proved valid and effective in improving the quality and standardization of final projects among PIAUD students.